Molecular treatment effects of alemtuzumab in skeletal muscles of patients with IBM. Issue 1 (December 2016) - Schmidt, Karsten; Kleinschnitz, Konstanze; Rakocevic, Goran; Dalakas, Marinos; Schmidt, Jens
Abstract Background Mechanisms of inflammation and protein accumulation are crucial in inclusion body myositis (IBM). Recent evidence demonstrated that intravenous immunoglobulin failed to suppress cell-stress mediators in IBM. Here we studied the molecular changes in skeletal muscle biopsies from patients with IBM before and after treatment with alemtuzumab. Methods Relevant inflammatory and degeneration-associated markers were assessed by quantitative-PCR and immunohistochemistry in repeated muscle biopsy specimens from patients with IBM, which had been treated in a previously published uncontrolled proof-of-concept trial with alemtuzumab. Results There were no significant changes of the mRNA expression levels of the pro-inflammatory chemokines CXCL-9, CCL-4, and the cytokines IFN-γ, TGF-β, TNF-α, and IL-1β. Similarly, the degeneration-associated molecules ubiquitin, APP and αB-crystallin did not substantially change. Although no overall beneficial treatment effect was noted except for a 6-month stabilization, some patients experienced a transient improvement in muscle strength. In such responders, a trend towards reduced expression of inflammatory markers was noted. In contrast, the expression remained unchanged in the others who did not experience any change. The expression levels of IL-1β and MHC-I correlated with the positive clinical effect. By immunohistochemistry, some inflammatory mediators like CD8, CXCL-9, and MHC-I were downmodulated. However, no consistent changes were noted for ubiquitin, nitrotyrosin and β-amyloid. Conclusions Alemtuzumab showed a trend towards downregulation of the expression of some inflammatory molecules in skeletal muscle of IBM patients but has no effect on several crucial markers of cell stress and degeneration. The data are helpful to explain the molecular treatment effects of future lymphocyte-targeted immunotherapies in IBM.